Mechanisms of biliary stricture and novel therapeutic strategies - Peng, Boming; Zhang, Jianquan; Xiang, Yang (Frontiers in Medicine, 2025)
Biliary stricture is a common yet complex pathological condition in clinical practice, which can be classified into iatrogenic and non-iatrogenic categories. Iatrogenic biliary strictures are mostly caused by cholecystectomy and hepatobiliary surgical procedures, while non-iatrogenic factors include immune-mediated, infectious, ischemic, genetic, idiopathic, and tumor-related causes. These factors induce damage to the biliary epithelium through various mechanisms, subsequently leading to bile stasis, inflammation, and fibrosis. The occurrence and progression of biliary strictures typically involve three major pathological processes: epithelial regeneration, inflammatory response, and fibrotic deposition. Following injury, the biliary epithelium can be repaired and maintained through mechanisms such as cholangiocyte proliferation, hepatocyte transdifferentiation, and activation of biliary stem/progenitor cells; meanwhile, the inflammatory response plays a dual role by promoting epithelial repair while also facilitating the progression of fibrosis. Multiple signaling pathways exert central regulatory roles throughout these processes. Currently, treatment strategies for biliary strictures have gradually evolved from traditional surgical interventions, such as hepaticojejunostomy and liver transplantation, to non-surgical approaches including immune modulation, bile acid metabolism regulation, and gut microbiota interventions. In recent years, novel therapeutic strategies for biliary strictures have emerged, including molecular therapies targeting fibrosis-related signaling pathways, gene-editing technologies, regenerative replacement therapies, and the development of advanced tissue-engineered scaffolds. These emerging approaches are expected to offer more efficient and safer solutions for the precision treatment of biliary strictures in the future.